Chromosome aberrations in plants as a monitoring system. - Grant, W F (1978)
The potential of higher plants as a first-tier assay system for detecting chemical mutagens is evaluated. The use of plant tissue (primarily root tips and pollen mother cells) for studying the induction of chromosomal aberrations is one of the oldest, simplest, most reliable, and inexpensive methods available. Specific types of abnormalities have been induced by different classes of pesticides. Chromosome clumping, contraction, stickiness, paling, fragmentation, dissolution, chromosome and chromatid bridges, C-mitosis, and endoploidy have been reported in the literature. Examples of cytogenetic studies with pesticides demonstrating the usefulness of higher plants as a monitoring system are reviewed. Pesticides which cause chromosome aberrations in plant cells also produce chromosome aberrations in cultured animal cells. Frequently, the aberrations are identical. For example, studies have shown that compounds which have a C-mitotic effect on plant cells have the same effect on animal cells. It is recommended that plant systems be accepted as a first-tier assay system for the detection of possible genetic damage by environmental chemicals.